2020
DOI: 10.1101/2020.01.28.922773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Courtship behaviour reveals temporal regularity is a critical social cue in mouse communication

Abstract: While animals navigating the real world face a barrage of complex sensory input, their brains have evolved to perceptually compress multidimensional information by selectively extracting the features relevant for survival. For instance, communication signals supporting social interactions in several mammalian species consist of acoustically complex sequences of vocalizations, however little is known about what information listeners extract from such timevarying sensory streams. Here, we utilize female mice's n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…The tempo manipulations lengthened or shortened both syllables and inter-syllable intervals (ISIs). Because a recent study in mice ( Perrodin et al, 2020 ) suggested that the regularity of ISI values might be crucial for the detection of male courtship songs by female mice, we next asked whether GPs used individual syllables or temporal patterns of calls for call categorization. First, as a low-level control, we replaced the ISIs of calls with silence instead of the low level of background noise present in recordings to ensure that GPs were not depending on any residual ISI information (silent ISI).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tempo manipulations lengthened or shortened both syllables and inter-syllable intervals (ISIs). Because a recent study in mice ( Perrodin et al, 2020 ) suggested that the regularity of ISI values might be crucial for the detection of male courtship songs by female mice, we next asked whether GPs used individual syllables or temporal patterns of calls for call categorization. First, as a low-level control, we replaced the ISIs of calls with silence instead of the low level of background noise present in recordings to ensure that GPs were not depending on any residual ISI information (silent ISI).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the specific parameters of a given call utterance might carry rich information about the identity ( Boinski and Mitchell, 1997 ; Miller et al, 2010 ; Gamba et al, 2012 ; Fukushima et al, 2015 ) and internal state of the caller as well as social context ( Seyfarth and Cheney, 2003 ; Coye et al, 2016 ), call category identity encompasses all these variations. In some behavioral situations, listeners might need to be sensitive to these specific parameter variations—for example, for courtship, female mice have been shown to exhibit a high preference for temporal regularity of male calls ( Perrodin et al, 2020 ). But in other situations, animals must and do generalize over this variability to extract call category identity, which is critical for providing an appropriate behavioral response.…”
Section: Introductionmentioning
confidence: 99%
“…The tempo manipulations lengthened or shortened both syllables and inter-syllable intervals (ISIs). Because a recent study in mice (Perrodin et al, 2020) suggested that regularity of ISI values might be crucial for detection of male courtship songs by female mice, we next asked whether GPs used individual syllables or temporal patterns of calls for call categorization. First, as a low-level control, we replaced the ISIs of calls with silence instead of the low level of 13 background noise present in recordings to ensure that GPs were not depending on any residual ISI information (silent ISI).…”
Section: Temporal Manipulations Had Little Effect On Model Performanc...mentioning
confidence: 99%
“…Whereas the specific parameters of a given call utterance might carry rich information about the identity (Boinski and Mitchell, 1997; Miller et al, 2010; Gamba et al, 2012; Fukushima et al, 2015) and internal state of the caller as well as social context (Seyfarth and Cheney, 2006; Coye et al, 2016), call category identity encompasses all these variations. In some behavioral situations, listeners might need to be sensitive to these specific parameter variations - for example, for courtship, female mice have been shown to exhibit a high preference for temporal regularity of male calls (Perrodin et al, 2020). But in other situations, animals must and do generalize over this variability to extract call identity, which is critical for providing an appropriate behavioral response.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades there has been a growing interest in the usage and signaling of vocalizations in mice, with large efforts going into studying the underlying neurobiological mechanisms for auditory processing (Pomerantz et al, 1983;Liu et al, 2003;Neilans et al, 2014;Perrodin et al, 2020;Holy and Guo, 2005), and the production of vocalizations (Arriaga et al, 2012;Chabout et al, 2016;Okobi et al, 2019;Zimmer et al, 2019;Gao et al, 2019;Tschida et al, 2019;Michael et al, 2020). The tools available for experiments in mice provide a promising model for studying the neural basis of vocalizations, as well as the effects of genes on the origin and development of vocal and neural anatomy (Grimsley et al, 2011;Bowers et al, 2013;Chabout et al, 2016;Tabler et al, The copyright holder for this preprint this version posted August 13, 2021. ; https://doi.org/10.1101/2021.08.13.456283 doi: bioRxiv preprint (Steinfath et al, 2021).…”
Section: Introductionmentioning
confidence: 99%